PENGARUH MODEL PEMBELAJARAN QAUNTUM LEARNING TERHADAP HASIL BELAJAR IPAS PADA MATERI MATA PENCAHARIAN PENDUDUK DI KELAS IV SD - Limbong, Ariana Damayanti; Sitohang, Risma (Universitas Negeri Medan, 2024)
This research was carried out with the aim of finding out the effect of the quantum learning model on the learning outcomes of Natural and Social Sciences in the livelihood material of the population in Class IV of SD Negeri 106810 Sampali. The type of research used is Pre-Experimental with a One Group Pretest-Posttest research design. The subjects in this research were 40 students in class IV. The data collection techniques used were interviews, test questions and documentation. Data analysis was carried out using normality tests, homogeneity tests and hypothesis tests. The results of the research show that the average of the pre-test scores is 61,875 and the average of the post-test data is 72,625. Based on the students' scores on the post-test data it is known There were 20 students who got grades in the complete category after being given treatment. In the hypothesis test, it was obtained 6,254>1,684 and according to the t test criteria, namely > . It can be concluded that this proves that the application of the Quantum Learning learning model has an influence on the learning outcomes of Natural and Social Sciences in the subject of population livelihoods in class IV of SD Negeri 106810 Sampali.